Molecular insights of Rhesus negative donors with DEL phenotype in National Blood Centre, Malaysia / Dr Mazura Bahari… [et al.] - Bahari, Mazura; Mustakim, Maimunah; Mastuk, Fahmi; Ramli, Safura (Research Management Institute (RMI), 2016)
Rhesus (Rh) blood group D antigen is the largest group of all 33 known blood group systems (Kappler-gratias et al. 2014). Rh blood group system divided into two groups which is RhD positive and RhD negative determined by the presence or absence of RhD protein respectively.Most blood groups are encoded by single genes with alleles that differ by only one or a few amino acids. On the contrary, the Rh gene encoded by two proteins thatare differing of 36 out of 417 amino acids (Van Kim, Colin, and Cartron 2006). Large number of different between this two proteins trigger to the strong antigenicity of the RhD protein though explains why exposure to RhD can result in a potent immune response in a D-negative individual. Both gene located in a tail-to-tail orientation toward the end of the short arm of chromosome 1 (p34- 36) with physical distance between 30 000 base pairs that contained SMP1 gene and Rhesus box (Wagner, Franz F, Flegel 2002). The RhD antigen can differ in both the quantity of antigen expressed and the qualitative nature of the antigen. Serological technique over the years has now been explained by more recent studies using molecular technique. The D negative phenotype caused mainly by a series of changes in the RhD protein, which alter the phenotype of the D antigen. Therefore, based on their phenotype and molecular structure, these RHD alleles are classified as true negative, partial D, weak D and DEL. DEL is the most weakly expressed of D antigen. Usually, 30 or less copies of the D antigen per RBCs will be express by DEL phenotype compare with 1500 to 7000 sites for weak D and 30,000 antigen sites for normal D (Li et al. 2009; Sandler et al. 2014; Wagner et al. 2005). The routine serological typing does not distinguish RhD negative from the DEL phenotype resulting most of DEL donors are typed as RhD-negative. Nowadays, molecular technique has widely used to reveal the weak expression of DEL phenotype. Frequencies of the RH gene complex not only showed differences in the ethnicity but also in the genetic background of the Rh antigen. Majority Caucasian that phenotype as RhD negative is associated with the deletion of RHD between the upstream and downstream Rhesus boxes but in Africans about 25% of RhD negative Africans have an inactive RHD gene of pseudogene (RHDqj) (C.-P., Shao. J-H Maas, M. Kohler 2002; Flegel 2011; Gu et al. 2014). In contrast in the Asian population, RHDqj is rare, and a certain percentage of RhD-negative individuals have DEL phenotype orRHD-CEDS hybrid gene(Chen et al. 2004; Gu et al. 2014). The prevalence of DEL is approximately30% in Asian RhDnegativedonors and 0.1% in Caucasian RhD(Nuchnoi et al. 2015)…